Reconfigurable Security Architecture (RESA) Based on PUF for FPGA-Based IoT Devices - Armin Babaei; Gregor Schiele; Michael Zohner (Sensors, 2022)
Cybersecurity is a challenge in the utilization of IoT devices. One of the main security functions that we need for IoT devices is authentication. In this work, we used physical unclonable function (PUF) technology to propose a lightweight authentication protocol for IoT devices with long lifetimes. Our focus in this project is a solution for FPGA-based IoT devices. We evaluated the resiliency of our solution against state-of-the-art machine learning attacks.